P157 Modelling the developmental trajectory of infant and child sleep. (7th October 2021) - Webb, L; Phillips, A; Roberts, J
Abstract: Introduction: Sleep is important for infant and child neurodevelopment, yet there is a lack of mechanistic understanding of what drives the changes in sleep over the early years of life. While sleep in the adult brain has been studied and modelled extensively, very little has been done in infants and children, mainly limited to descriptive studies of sleep behaviour. Methods: We adapted an existing, physiologically based model of adult sleep to study infant and child sleep behaviour. We compared modelled sleep behaviour to published data on sleep characteristics over a range of ages, both cross sectional from 0 to 5 years and densely-sampled individual data in the first year of life. We performed Bayesian inference to estimate the likely physiological parameters underpinning population-level diversity in sleep characteristics as a function of age from 0 to 5 years. We also fitted the model to individual sleep architecture in the first year of life. Results: The empirically observed decrease in total sleep duration and consolidation of sleep bouts with increasing age are well explained by decreases in the constant inhibitory input to the ventrolateral preoptic nucleus and increases in the characteristic somnogen clearance time during sleep. Further, our model produced realistic sleep-wake dynamics consistent with early maturation of sleep in the heavily sampled, single infant data. Discussion: Our results show that a greater understanding of the neurophysiology of sleep in infants and children can be achieved through the use of physiologically based models.